Economic viability of large-scale solar PV implementation in the Nordic power market: Case Finland - Kankanamge, Dilshika Heenatigala; Jääskeläinen, Jaakko; Jouttijärvi, Sami; Syri, Sanna (ELSEVIER, 2026)
This study analyses how the rapid growth of utility-scale solar PV in the Nordic region will impact its economic viability by 2030, using Finland as a case study. The analysis is based on modelling the Nordic electricity market. Solar energy is crucial for the energy transition in the Nordic region; however, high penetration levels pose significant economic challenges. The lack of feed-in tariffs for solar PV, limited energy system flexibility, high shares of nuclear and wind power and ambitious solar expansion plans make Finland a topical case study. Using PLEXOS advanced electricity market simulation tool, this study models the Nordic and Baltic multinational electricity system in detail and its connections to the Central Western European power market. The study includes significant electricity demand changes from rapid increases in electric vehicles, district heating electrification, and hydrogen production. Multiple scenarios representing different solar PV levels across the Nordic regions are analysed by 2030, including one scenario with various shares of vertically mounted, east-westoriented bifacial solar PV. Results indicate that large-scale solar PV integration in the Nordic region could collapse Finnish electricity prices, specifically in the summer months. This expansion would reduce solar capture rates to 40% by 2030, highlighting the solar cannibalisation in Finland. These findings indicate the potential economic risks of extensive solar PV deployment and the need for market adaptation. Integrating vertical bifacial panels to adjust the PV production profile and optimising the electric vehicle charging are found to be important to improve the economic viability of solar generation.